Shifts in pond water bacterial communities are associated with the health status of sea bass (Lateolabrax maculatus) - Yiqin Deng (Elsevier, 2021)
Sea bass (Lateolabrax maculatus) is the third largest maricultured fish in terms of abundance on mainland China. However, sea bass has been reported to be susceptible to infection by a series of microbial pathogens, endangering the sustainable development of its mariculture. Therefore, there is a need to clarify the relationship between the occurrence of sea bass disease and the surrounding microbial communities, and to verify particular bacterial assemblages that indicate its health status (either healthy or diseased), with important implications for the sustainable development of sea bass aquaculture. In the current study, water samples were collected from two open-air aquaculture ponds with high and low sea mass mortality in the Doumen district of Zhuhai, South China. The contrasting bacterial community composition and function of the two sea bass ponds, and the driving effects of the environmental conditions were investigated. There was a significantly positively correlation between community structure and community function, with both in the high-mortality pond being significantly different (P < 0.05) from those in the low-mortality pond, with temperature, PO43–, dissolved oxygen, and NO3– driving the difference. The relative abundance of five potential disease indicators (Sporichthyaceae, Saprospiraceae, Chitinophagaceae, Microbacteriaceae, and Burkholderiaceae) increased, whereas that of the potential health indicator Moraxellaceae decreased in the high-mortality pond. These six indicators are likely to affect sea bass survivability by being involved in the decomposition of animal remains, producing antibiotics, and degrading other organic materials. Thus, the results of the current study provide indirect evidence for the use of aquatic microbiota composition as a biological indicator to evaluate the occurrence of sea bass diseases.